Reality check (Colorado State Library Book Club Collection): a novel (Poppy/Little Brown, 2011)
When a television executive signs Long Island sixteen-year-old Charlie and her three best friends to be the stars of a new reality television show, their lives are suddenly not the same.

I funny (Colorado State Library Book Club Collection): a middle school story (Middle school story, ,, 2012)
Resolving to become the world's greatest stand-up comedian despite less-than-funny challenges in his life, wheelchair-bound middle school student Jamie Grimm endures bullying from his mean-spirited cousin and hopes he will be fairly judged when he enters a local comedy contest.